A proliferation-inducing ligand (APRIL) level among risk factors of ocular involvement in patients with Behçet’s disease - Rasha M. Ghaleb; Hanan S. Gad; Mohamed I. Abdallah; Zaki M. Zaki; Jehan A. Mahmoud (Rheumatology)
Introduction Ocular involvement is quite common in Behçet’s disease (BD) and may cause crucial functional complications. Even though the mechanisms of BD remain unclear, advances in genetic and immunological fields have improved our understanding of the immunopathogenesis of BD ocular involvement. Little is known about the expression of a proliferation-inducing ligand (APRIL) in terms of ocular involvement in BD. The objective of this study was to determine whether serum APRIL concentrations are associated with ocular involvement in patients with BD.